Burnout and Alcohol Abuse/Dependence Among U.S. Medical Students. (September 2016) - Jackson, Eric R.; Shanafelt, Tait D.; Hasan, Omar; Satele, Daniel V.; Dyrbye, Liselotte N.
Abstract : Purpose: To explore the relationship between alcohol abuse/dependence with burnout and other forms of distress among a national cohort of medical students. Method: In 2012, the authors completed a national survey of medical students from the American Medical Association's Physician Masterfile containing validated items assessing alcohol abuse/dependence, burnout, depression, suicidality, quality of life (QOL), and fatigue. Descriptive and comparative statistical analyses were computed, including chi-square and multivariate logistic regression, to determine relationships between variables. Results: Of the 12, 500 students, 4, 402 (35.2%) responded. Of these, 1, 411 (32.4%) met diagnostic criteria for alcohol abuse/dependence. Students who were burned out ( P = .01), depressed ( P = .01), or reported low mental ( P =.03) or emotional ( P = .016) QOL were more likely to have alcohol abuse/dependence. Emotional exhaustion and depersonalization domains of burnout were strongly associated with alcohol abuse/dependence. On multivariate analysis, burnout (OR 1.20; 95% CI 1.05–1.37; P < .01), having 50, 000 to 100, 000 (OR 1.21 versus < 50, 000; CI 1.02–1.44; P < .05) or > 100, 000 (OR 1.27 versus < 50, 000; CI 1.08–1.48; P < .01) of educational debt, being unmarried (OR 1.89; CI 1.57–2.27; P < .001), and being younger (for every five years, OR 1.15; CI 1.02–1.28; P = .01) were independently associated with increased risk for alcohol abuse/dependence. Conclusions: Burnout was strongly related to alcohol abuse/dependence among sampled medical students and increased educational debt predicted a higher risk. A multifaceted approach addressing burnout, medical education costs, and alcohol use is needed.